1969
DOI: 10.2527/jas1969.283418x
|View full text |Cite
|
Sign up to set email alerts
|

DDT Residues in Beef Cows Fed Apple Pomace

Abstract: It has replaced all of the roughage normally used for wintering beef cows (Burris and Priode, 1957). However, in the past, apple pomace has contained up to 40 parts per million (ppm) residues of DDT [1, 1, 1-trichloro-2, 2-bis (p-chlorophenyl) ethane] which accumulated (75.7 ppm) in omental fat of beef steers (Bovard et al., 1961). Currently the U. S. Food and Drug Administration tolerance of DDT residues is 7.0 ppm in animal fat and, therefore, apple pomace is not being used as a feed source. Recently, many a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The accumulation of DDT residues in the depot fat of beef cows fed apple pomace was below the current tolerance of 5 ppm s and similar to that observed in the second experiment of an earlier study by Rumsey et al (1969). After correction for differences in pesticide intake, residue accumulation appeared to be greater in the heart and external rib fats when the pesticides were added to the simulated apple pomace diet (trial 2) than when they were present as a contaminant in apple pomace (trial 1).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The accumulation of DDT residues in the depot fat of beef cows fed apple pomace was below the current tolerance of 5 ppm s and similar to that observed in the second experiment of an earlier study by Rumsey et al (1969). After correction for differences in pesticide intake, residue accumulation appeared to be greater in the heart and external rib fats when the pesticides were added to the simulated apple pomace diet (trial 2) than when they were present as a contaminant in apple pomace (trial 1).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, it is important to know the nature and relative levels of residues in various parts of our environment, particularly if potential sources of animal feed are involved. Apple pomace, a potential feed for beef cattle, was shown by Rumsey et al (1969) to contain DDT, dicofol and tetradifon residues at levels that caused residue accumulation in fat depots of beef cows. The present study indicated that apple pomace may present an additional residue problem because of the variation in the concentration of pesticides in the apple pomace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the extraction of samples with petroleum ether, the extracts were prepared and analyzed by using a hexane-acetonitrile partitioning and florisil column cleanup as described by Mills (1961) and the gas chromatographic conditions described by Rumsey et al (1969). The percentage of ether extract was determined for all depot fat tissues based on the above petroleum ether extraction.…”
Section: Methodsmentioning
confidence: 99%